The Gay Archipelago : Sexuality and Nation in Indonesia. - Boellstorff, Tom. (Princeton : Princeton University Press, 2005)
The Gay Archipelago is the first book-length exploration of the lives of gay men in Indonesia, the world's fourth most populous nation and home to more Muslims than any other country. Based on a range of field methods, it explores how Indonesian gay and lesbian identities are shaped by nationalism and globalization. Yet the case of gay and lesbian Indonesians also compels us to ask more fundamental questions about how we decide when two things are ""the same"" or ""different."" The book thus examines the possibilities of an ""archipelagic"" perspective on sameness and difference.</p.
Cover; Title; Copyright; Dedication; Contents; List of Illustrations; Acknowledgments; Note on Indonesian Terms and Italicization; PART ONE The Indonesian Subject; CHAPTER ONE: Introduction; CHAPTER TWO: Historical Temptations; CHAPTER THREE: Dubbing Culture; PART TWO Opening to Gay and Lesbi Worlds; CHAPTER FOUR: Islands of Desire; CHAPTER FIVE: Geographies of Belonging; CHAPTER SIX: Practices of Self, Tests of Faith; PART THREE Sexuality and Nation; CHAPTER SEVEN: The Postcolonial State and Gay and Lesbi Subjectivities; CHAPTER EIGHT: The Gay Archipelago; Notes; Works Cited; Index.
Print version record.
Includes bibliographical references (pages 243-265) and index.
Keywords: Gay men -- Indonesia -- Identity; Lesbians -- Indonesia -- Identity; Gay men -- Indonesia -- Social conditions; Lesbians -- Indonesia -- Social conditions; Gender identity -- Indonesia; Homosexuality -- Political aspects -- Indonesia; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Gay Studies; Gay men -- Identity; Gay men -- Social conditions; Gender identity; Homosexuality -- Political aspects; Lesbians -- Identity; Lesbians -- Social conditions; Indonesia; Electronic books; Electronic books